2015
DOI: 10.1515/cmble-2015-0048
|View full text |Cite
|
Sign up to set email alerts
|

Death domain associated protein (Daxx), a multi-functional protein

Abstract: Death domain associated protein (Daxx), a multi-functional protein, plays an important role in transcriptional regulation, cell apoptosis, carcinogenesis, anti-virus infection and so on. However, its regulatory mechanisms for both cell survival and apoptosis remain largely obscure. Our review of recent studies shows that Daxx has many interesting functional dualities and can provide a reference for further research on Daxx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
1
13
0
2
Order By: Relevance
“…Previous research has shown that the ox-LDLs is closely related to ASK1-induced apoptosis. 55 Another study demonstrated that phosphorylated ASK1 plays a key role in atherosclerosis development, 56 and that an ASK inhibitor (AGI-1067) exerts an antiinflammatory effect by inhibiting the dissociation of thioredoxin in vascular endothelial cells. 57 In addition, another study showed that thioredoxin-1 (Trx-1) could protect macrophages from ox-LDL-induced foam cell formation and apoptosis by interacting with ASK1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the ox-LDLs is closely related to ASK1-induced apoptosis. 55 Another study demonstrated that phosphorylated ASK1 plays a key role in atherosclerosis development, 56 and that an ASK inhibitor (AGI-1067) exerts an antiinflammatory effect by inhibiting the dissociation of thioredoxin in vascular endothelial cells. 57 In addition, another study showed that thioredoxin-1 (Trx-1) could protect macrophages from ox-LDL-induced foam cell formation and apoptosis by interacting with ASK1.…”
Section: Discussionmentioning
confidence: 99%
“…The present results verified the important role of DAXX in regulating high Pi-induced HUVECs apoptosis and may provide a novel opportunity to treat high Pi-induced endothelial cell apoptosis. DAXX can both promote and suppress apoptosis (Tang, Wan & Wu, 2015), and the specific mechanism of DAXX remains unclear. DAXX largely localizes to the nucleus of un-stimulated cells and exerts an anti-apoptotic effect in the nucleus (Tang, Wan & Wu, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…DAXX can both promote and suppress apoptosis (Tang, Wan & Wu, 2015), and the specific mechanism of DAXX remains unclear. DAXX largely localizes to the nucleus of un-stimulated cells and exerts an anti-apoptotic effect in the nucleus (Tang, Wan & Wu, 2015). Dionne et al (2013) demonstrated that DAXX has an anti-apoptotic effect on the HUVECs were overexpressed with DAXX in the presence or absence of U0126 (100 ng/mL), and then cell apoptosis was assessed using flow cytometric analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daxx is a multifunctional, ubiquitously expressed and highly conserved protein through evolution. It has no enzymatic activity, but rather acts as a scaffold to bridge different proteins, thus regulating their function (reviewed in [ 41 , 42 , 43 ]). Although this multifunctional adapter is present in the cytoplasm, it is mainly expressed in the nucleus, where it localizes within promyelocytic leukemia protein (PML) nuclear bodies.…”
Section: Introductionmentioning
confidence: 99%